Oregano essential oil (Origanum vulgare) induces death in a resistant strain of Leishmania infantum isolated from a naturally infected dog through increased production of reactive oxygen species, mitochondrial damage and cell metabolic disruption - Rodrigues, Ana Carolina Jacob; Lazarin Bidoia, Danielle; Carloto, Amanda Cristina Machado; Concato-Lopes, Virgínia Márcia; Detoni, Mariana Barbosa; Cruz, Ellen Mayara Souza; Suzuki, Sara Mayumi; Inoue, Fabricio Seidy; Silva, Taylon Felipe; Figueiredo, Fabiano Borges; Pavanelli, Wander Rogério (Frontiers in Cellular and Infection Microbiology, 2025)
Background: Leishmaniasis is a neglected tropical disease caused by protozoa of the Leishmania genus, transmitted by phlebotomine sandflies. Clinical manifestations vary depending on the parasite’s species and the host’s immune system, ranging from self-healing skin lesions to lethal visceral diseases. Visceral leishmaniasis (VL), mainly caused by L. infantum and L. donovani, is a serious public health issue. Conventional treatment is challenging due to toxicity, long duration, and resistance, highlighting the need for alternative therapies. Oregano essential oil (OEO) has biological effects, including antibacterial, antifungal, and antioxidant actions, making it a potential leishmanicidal agent. To evaluate its activity, promastigotes of two L. infantum strains were tested: MS (from naturally infected dogs in Brazil) and a reference strain (MCAN/BR/97/p142). The IC50 values were 12.53 µg/mL and 43.61 µg/mL, respectively, while amphotericin B (AmB) showed lower IC50 values (0.1453 µg/mL and 0.2126 µg/mL). OEO treatment increased reactive oxygen species (ROS) production, mitochondrial damage, lipid droplet accumulation, and autophagic vacuoles, indicating intense cellular stress. Additionally, apoptosis markers such as phosphatidylserine exposure and membrane permeabilization were detected. Fluorescence, scanning (SEM), and transmission (TEM) microscopy revealed morphological and ultrastructural alterations, including membrane blebbing, flagellar damage, intracellular content leakage, and mitochondrial swelling. To assess its anti-amastigote effect, THP-1 cells infected with L. infantum strains were treated with OEO. The MS strain showed a lower infection rate but a higher parasite load per macrophage. All tested concentrations (25, 50, and 75 μg/mL) reduced both the number of infected macrophages and intracellular amastigotes. Thus, OEO exhibits leishmanicidal activity in both promastigote and amastigote forms of L. infantum, inducing metabolic disruption and cell death, even in strains from naturally infected dogs. These findings highlight OEO’s potential as an alternative treatment for VL.